Identifying extreme pluvials in the last millennia using optical dating of single grains of quartz from shorelines on Australia's largest lake. (January 2018) - Cohen, Tim J; Meyer, Michael C; May, Jan-Hendrik
The filling of Kati Thanda-Lake Eyre (KT-LE), Australia's 'inland sea' has captured scientific and cultural interest for over a century and a half. However, despite the presence of multiple shorelines around the modern playa at or near the modern maximum lake-filling levels, no quantitative estimates of major late-Holocene filling events have ever been documented. We develop a preliminary chronological data set using single-grain optically stimulated luminescence (OSL) on lake shoreline samples in order to determine the timing of large lake-filling events (equivalent to 1974 Common Era (CE) as Australia's wettest year on record) for KT-LE, Australia's largest lake basin. Despite quartz grains with very low natural dose luminescence (Ln) signal, we derive palaeodoses from geologically recent deposits (decades to centuries) using standard rejection criteria and highlight no signs of partial bleaching but occasional bioturbation in modern deposits. Major modern filling episodes, such as the1974 and 1949/1950 filling events, are successfully captured in the geochronological record, as are two major lake-filling episodes in 1854 ± 21 CE years and 1598–1654 CE. Two additional periods of potential lake-filling events have been identified at 1.2 ± 0.09 and 1.9 ± 0.14 ka, but stratigraphic control on these events is less robust. These chronostratigraphic records, while discontinuous, provide important hydrological evidence for extreme pluvial events akin to 1974 or 1949/1950, and the approach holds promise for identifying climate extremes and landscape response over the late Holocene.